Ability of the Public to Recognize Dogs Considered to Be Dangerous under the Dangerous Dogs Act in the United Kingdom. Issue 3 (3rd July 2019) - Webster, Catherine A.; Farnworth, Mark J.
ABSTRACT: Canine aggression came into the public eye in the United Kingdom in the late 1980s prompting enactment of the UK Dangerous Dogs Act, which prohibits four breeds or "types" of dogs. The act faced strong opposition surrounding correct identification of prohibited dogs. A questionnaire was distributed to the public via an online platform, especially targetting those who have worked with dogs. The questionnaire assessed respondents' abilities to identify the four banned types of dogs from other breeds and their capability to identify Pit Bull Terrier types from other similar dog types. Identification of both banned breeds, F (1, 20) = 57.746, p < .001, and bull breeds, F (1, 20) = 9.293, p = .006, was significantly lower than identification of other breeds. Recognition of Pit Bull Terrier types from similar types of dogs was generally poor, although people in a dog-related profession, as opposed to those in other professions, could correctly distinguish more pit bull-type dogs (U = 46, 164.0, n 1 = 187, n 2 = 575, p = .003). Findings suggest public understanding of dangerous dogs is poor, and it may impact societal perceptions of dogs more widely.